Contribuições dos espaços não formais de aprendizagem para alfabetização científica : uma experiência no Zoológico de Goiânia - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
The Goiânia Zoological Park (PZG) is a non-formal learning space with multiple opportunities to develop educational activities. PZG constantly receives visits from a large number of students, both from public and private schools from all over the state of Goiás. a qualitative and quantitative historical review, as well as through the report of an experience conducted with students from two classes of the 5th year of elementary school in the state education system of Goiás. Thus, the dissertation was structured in two articles, so that each of these two research proposals compose an article. For the first article, data were obtained through literature review and document analysis of the PZG. In this sense, it was possible to see that over time, according to the development of human thought, zoos stopped being places of exhibitionism and spectacles, when they were created, becoming spaces for conservation, research, database genetics, Education and animal welfare, in the present time. It was also verified a significant number of institutionalized and non-institutionalized groups that visit the PZG, with emphasis on Basic Education students from municipal schools. Analyzing the projects developed by the PZG environmental educators, it was noticed the connection between the themes of the activities offered and the learning expectations of the schools, because they choose the projects to be developed with the students according to their teaching interest so that they can reach the proposed objectives through bringing the students closer to the object of study. The second article was conducted in five stages: conversation circle, survey of prior knowledge through questionnaires and drawings, visit to the PZG, post-visit knowledge verification through questionnaires and drawings, and socialization of knowledge to the community school. The roundtable revealed that few students knew about the PZG and that the opportunity to visit aroused interest in the topic. During the visit, students demonstrated excitement and enthusiasm through questions and comments. Our comparative analysis of pre- and post-visit questionnaires and designs, showed that both groups had good use of activities with expansion of knowledge about the Fauna and Flora of the Cerrado. Elements and information presented by the environmental educators during the lecture and along the educational trail were verified in the evaluation instruments, such aspeculiar characteristics of the Cerrado Flora and typical animals of the biome, which had been little remembered before the visit. Given the results obtained, it is possible to conclude that the PZG can function as a non-formal learning space that contributes to the scientific literacy process of students who visit it. As educational products of this dissertation, a didactic sequence was elaborated contemplating the Food Chain theme and an educational game entitled Cerrado Fauna – Quem é o bicho? Contemplating the characteristics of animals in the Cerrado, which was developed in three versions: letters, projection and mobile application. Such resources aim to contribute to teachers in approaching the topic in a playful way, in order to arouse greater interest from students.
Contributions of non-formal learning for scientific literacy : an experience at the Goiânia Zoo
Keywords: Educação ambiental; Fauna; Flora; Visita pedagógica; Relato de experiência; Environmental education; Fauna; Flora; Education visit; Alfabetização científica; Scientific literacy; EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS BIOLOGICAS